Multifunctional GelMA platforms with nanomaterials for advanced tissue therapeutics - Amal George Kurian (KeAi Communications Co., Ltd., 2022)
Polymeric hydrogels are fascinating platforms as 3D scaffolds for tissue repair and delivery systems of therapeutic molecules and cells. Among others, methacrylated gelatin (GelMA) has become a representative hydrogel formulation, finding various biomedical applications. Recent efforts on GelMA-based hydrogels have been devoted to combining them with bioactive and functional nanomaterials, aiming to provide enhanced physicochemical and biological properties to GelMA. The benefits of this approach are multiple: i) reinforcing mechanical properties, ii) modulating viscoelastic property to allow 3D printability of bio-inks, iii) rendering electrical/magnetic property to produce electro-/magneto-active hydrogels for the repair of specific tissues (e.g., muscle, nerve), iv) providing stimuli-responsiveness to actively deliver therapeutic molecules, and v) endowing therapeutic capacity in tissue repair process (e.g., antioxidant effects). The nanomaterial-combined GelMA systems have shown significantly enhanced and extraordinary behaviors in various tissues (bone, skin, cardiac, and nerve) that are rarely observable with GelMA. Here we systematically review these recent efforts in nanomaterials-combined GelMA hydrogels that are considered as next-generation multifunctional platforms for tissue therapeutics. The approaches used in GelMA can also apply to other existing polymeric hydrogel systems.